2009
DOI: 10.1002/art.24555
|View full text |Cite
|
Sign up to set email alerts
|

Elevated serum interferon‐α activity in juvenile dermatomyositis: Associations with disease activity at diagnosis and after thirty‐six months of therapy

Abstract: Objective. Interferon-␣ (IFN␣) has been implicated in the pathogenesis of juvenile dermatomyositis (DM). The aim of this study was to examine serum IFN␣ activity in a cohort of children with juvenile DM to determine relationships between IFN␣ and indicators of disease activity and severity.Methods. Thirty-nine children with definite/ probable juvenile DM were included in the study. Serum samples were obtained at the time of diagnosis from 18 untreated patients with juvenile DM. Second samples from 11 of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
0
1

Year Published

2010
2010
2013
2013

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 116 publications
(81 citation statements)
references
References 37 publications
3
77
0
1
Order By: Relevance
“…As in the example above, a positive correlation between serum IFN-α and TNF-α in SLE was observed [25]. In JDM, the TNF-α -308A allele that has been linked to higher TNF-α production [29] was associated with increased serum IFN-α levels [26,30]. In addition, besides known up-regulation of TNF-α in RA synovium, the increased expression of type I IFN has been also reported in the synovium of patients with RA [31].…”
Section: Cross-regulation Between Type I Ifn and Tnf-αmentioning
confidence: 54%
See 1 more Smart Citation
“…As in the example above, a positive correlation between serum IFN-α and TNF-α in SLE was observed [25]. In JDM, the TNF-α -308A allele that has been linked to higher TNF-α production [29] was associated with increased serum IFN-α levels [26,30]. In addition, besides known up-regulation of TNF-α in RA synovium, the increased expression of type I IFN has been also reported in the synovium of patients with RA [31].…”
Section: Cross-regulation Between Type I Ifn and Tnf-αmentioning
confidence: 54%
“…A genetic association study demonstrated that the PTPN polymorphism was associated with skewing of cytokine profiles toward higher IFN-α activity and lower TNF-α levels in vivo in patients with SLE. Moreover, in untreated patients with juvenile dermatomyositis (JDM), serum IFN-α levels was shown to be associated with the TNF-α G-308A promoter polymorphism [26]. In sarcoidosis, the presence of a TNF-α -308A variant allele was also reported to be associated with the susceptibility to and risk of sarcoidosis [27,28].…”
Section: Cross-regulation Between Type I Ifn and Tnf-αmentioning
confidence: 99%
“…Recently, it has been reported that serum IFN-a activity is associated with higher serum levels of muscle-derived enzymes in DM patients [10] and that genes induced by IFN-a/b are highly expressed in DM muscle biopsies compared with muscle from patients with other inflammatory myopathies [11]. Moreover, IFN-a treatment may be associated with the onset of DM [12].…”
Section: Discussionmentioning
confidence: 97%
“…Interferon causes inappropriate increase in the expression of MHC-I and induces proinflammatory cytokines and chemokines (IL-5, IFN-γ) and maybe participating in the initiation of the inflammatory process, as its activity is directly correlated to a higher elevation of serum muscle enzymes and inversely with the time of non-treated disease. 18 Plasmacytoid dendritic cells, which regulate both the innate and acquired immune response, especially against virus, were equally identified in inflammatory infiltrates of JDM patients; they would lead to an increase in the production of IFN and they would be actively involved in disease progression by modulating the function of T lymphocytes in muscular blood vessels, participating in the initiation and maintenance of the characteristic autoimmune inflammatory lesions. 3,11,19,20 …”
Section: Pathogenesismentioning
confidence: 99%
“…It is important to point out that vasculitic lesions, calcinosis and lipodystrophy are more common in children than in adults, being more prevalent in those with the TNF-α 308A allele. 6,27,18 Calcinosis affects 30 to 70% of patients, especially in elbows and knees. It develops in up to a mean of 3.4 years after the onset of the disease and results from the accumulation of hydroxyapatite after release of mitochondrial calcium by the damaged muscle, leading to mineralization.…”
Section: Typical Cutaneous Changesmentioning
confidence: 99%